2007
DOI: 10.1016/j.ejheart.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A critical re‐appraisal of different ways of selecting ambulatory patients with suspected heart failure for echocardiography

Abstract: Background: ECG and BNP have been assessed as screening tests for LVSD and heart failure. However, echocardiography also provides information about valvular disease and LVH. We assessed how good these screening tests are in identifying whether the subsequent echocardiogram will have any significant abnormality. Aims: To re-appraise the ECG and BNP as screening tests for echocardiography since there are important practical deficiencies in our current knowledge in this area. Methods: General practitioners referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Similarly in Holland, 13 the incidence of moderate or severe valve disease was 31% with murmur, 23% with breathlessness and 28% with peripheral oedema. In a Scottish study, 20 the incidence of all valve disease in patients with suspected heart failure was 46% which was substantially higher than the incidence of LV systolic dysfunction, 8%. The incidence of valve disease was similar to the EuroHeart Failure 21 survey, but the study showed that the valve disease was primary in 58 (67%) and secondary in 28 (33%).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Similarly in Holland, 13 the incidence of moderate or severe valve disease was 31% with murmur, 23% with breathlessness and 28% with peripheral oedema. In a Scottish study, 20 the incidence of all valve disease in patients with suspected heart failure was 46% which was substantially higher than the incidence of LV systolic dysfunction, 8%. The incidence of valve disease was similar to the EuroHeart Failure 21 survey, but the study showed that the valve disease was primary in 58 (67%) and secondary in 28 (33%).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, this combined strategy remains to be tested prospectively, particularly in populations with higher prevalence of cardiac dysfunction in which the yield of a biomarker-based screening strategy may be higher. Even if electrocardiography and natriuretic peptide screening are adequate in determining the probability of the presence of left ventricular systolic dysfunction, the challenge is to adequately screen for other structural abnormalities such as valvular disease or left ventricular hypertrophy that may ultimately lead to progression of cardiac dysfunction (25). Although screening asymptomatic patients at risk, detecting surrogate markers, and initiating early treatment to prevent heart failure appears to be an obvious strategy, there are several challenges that remain: very large sample sizes are needed to demonstrate benefits of early treatment, the most cost-effectiveness manner of screening patients is still unsettled, and the cost of screening is not uniformly covered by insurance or other payers.…”
Section: Patients At Risk To Develop Heart Failure (Stages a And B)mentioning
confidence: 99%
“…However, it should be noted that echocardiography will not only give information about left ventricular function, but also valve function and the presence of left ventricular hypertrophy. 20 Further advantages of BNP relate to its convenience and this was highlighted by a number of GPs who took part in this pilot project. Travelling to a hospital or clinic for echocardiography can be difficult for some patients and almost impossible for others, such as the frail elderly, especially those in nursing homes or those in remote or rural populations.…”
Section: -5mentioning
confidence: 99%
“…20 For comparison, a standard cost for an ECG was assumed to be £30 and an echocardiogram £72. 21 The number of samples generated within the eight GP surgeries and their associated population was extrapolated to estimate the numbers likely to be generated per million population per year.…”
Section: Estimates Of Costmentioning
confidence: 99%